Innovative methods of maintaining operation records using the online Google spreadsheet - B A Ramesh; Singaravelu Viswanathan; Souparna Manjunath; Deyonna Deepthi Fernandez; Candy Priyadarshini; Gaurav B Shetty (Formosan Journal of Surgery, 2019)
Background: Maintaining an operation record in any surgical department is mandatory. The current method is to make entries in a designated register manually. However, this method has disadvantages such as space occupancy, high maintenance cost, and difficulty in record compilation. Proper storing of medical records is necessary for future reference. We found that using the free online, Google spreadsheet for maintaining surgical records is an innovative and effective method. Methods: Online Google spreadsheet entry September 2017 to August 2018 is compared with manual entry done from September 2016 to August 2017. Results: This online method has the following advantages: fewer errors, low cost, free maintenance, and easy record compilation as per requirements. Finally, filters can be applied, and separate numbers for each category can be obtained. Conclusion: The proposed method is useful, low cost, and versatile way of storing and retrieving operative records.